The Influence Of Communication Effectiveness And Work Discipline On Employee Peformamce In The Phylon Injection Department At PTAdis Dimension Footwear Tangerang Regency - Oktavia, Mia; Fahmi, Khaerul; Setiawan, Temmy (Faculty of Science and Technology University of Pramita Indonesia, 2026)
This study aims to determine: (1) the partial effect of communication effectiveness on employee performance; (2) the partial effect of work discipline on employee performance; (3) the simultaneous effect of communication effectiveness and work discipline on employee performance.This study uses a quantitative descriptive method, which describes variables as they are, sample consisted of 57 respondentsThe results of this study indicate that (1) partially, communication effectiveness significantly influences the performance of employees in the Phylon Injection department at PT. Adis Dimension Footwear Balaraja-Tangerang. (2) Partially, work discipline significantly influences the performance of employees in the Phylon Injection section at PT. Adis Dimension Footwear Balaraja-Tangerang, (3) Simultaneously, work discipline and motivation significantly influence the performance of employees in the Phylon Injection section at PT. Adis Dimension Footwear Balaraja-Tangerang.